The Relationship Between Social Problem-Solving and Passive-Aggressive Behavior Among Adolescents - Gál Zita; Nagy Márió Tibor; F. Takács István; Kasik László (2025)
The aim of the study was to investigate the relationship between passive-aggressive behavior and social problem-solving among Hungarian adolescents (16- and 18-year-olds, N = 496). The Passive Aggression Scale (PAS) was used to explore the characteristics of criticism, ignoring, and sabotage, and the Social Problem-Solving Inventory–Revised (SPSI–R) was employed to measure negative and positive problem orientations and rational, impulsive, and avoidant problem-solving styles. Both questionnaires performed reliably for both ages. The results show that 18-year-olds are more likely to have a negative problem orientation. Both age groups show a similarly strong positive relationship between criticism–impulsivity and ignoring–rationality. Based on a latent profile analysis, two problem-solving profiles (mixed and positive rational) were distinguished for 16-year-olds and three (mixed, positive rational, and negative avoidant) for 18-year-olds. Only the profiles obtained for the older age groups differ in passive-aggressive characteristics: criticism is most common for impulsive avoiders, ignoring is least typical of positive rationalists, and sabotage is most characteristic of mixed profiles. Developmental and socio-psychological features are usually well understood in these patterns, but a measure of various passive-aggressive behaviors is needed that is specific to adolescents.
Keywords: Pszichológia; Oktatástudomány